Mental Toughness dan Competitive Anxiety pada Atlet Bola Voli - Algani, Panji Wahyu; Yuniardi, Muhammad Salis; Masturah, Alifah Nabilah (University of Muhammadiyah Malang, 2018)
Abstrak. Competitive anxiety merupakan suatu hal negatif dalam menghadapi kompetisi karena dapat menurunkan capaian prestasi dan hal ini diindikasi salah satunya terkait dengan mental toughness atau kemampuan untuk bersikap positif ketika menghadapi suatu tekanan khususnya dalam sebuah pertandingan. Penelitian ini bertujuan untuk menguji hubungan antara mental toughness dengan competitive anxiety pada atlet bola voli. Terdapat 118 responden yang mengisi lengkap dan data selanjutanya dianalisis melalui product moment correlation Pearson SPSS 21.0. Hasil menunjukkan adanya hubungan negatif yang signifikan antara mental toughness dengan competitive anxiety (r = -0,670 dan p < 0,001). Semakin mampu seorang atlit untuk bersikap positif terhadap tekanan maka semakin rendah kecemasannya menghadapi kompetisi.Â Kata kunci: mental toughness, competitive anxiety, atletÂ Abstract. Competitive anxiety could distract concentration and eventually could decrease achievement. It has been indicated that competitive anxiety is related to mental toughness or an ability to develop a positive attitude in handling pressure particularly a competition. This study aimed to investigate the relationship between mental toughness and competitive anxiety. This study recruited 118 volleyball athletes and their data subsequently was analysed through product moment correlation Pearson SPSS 21.0. The result revealed that there was a significant negative correlation between mental toughness and competitive anxiety behavior (r = -0,670 and p < 0,001). More able to positively perceive pressure and handling the situation, athletes would be less anxiety in facing the competition.Â Keyword: mental toughness, competitive anxiety, athletes